A Practical Method for No-Reflow Treatment - Mustafa Cetin; Emrullah Kiziltunc; Zehra Güven Cetin; Harun Kundi; Birsen Gulkan; Hülya Cicekcioglu (Case Reports in Cardiology)
No-reflow is an undesirable result of percutaneous coronary interventions. Vasoactive drug administration at the distal part of the coronary artery is suggested as a therapeutic option for no-reflow treatment. Here, we represent two cases of successful no-reflow management with previously used monorail balloon at the same procedure as a hand-made distal infusion catheter.